Decentralization of the provision of health services to people living with HIV/AIDS in rural China: the case of three counties - Zhang Yurong; Miège Pierre; Zhang Xiulan (BMC, 2011)
Abstract This study is based on a large-scale household survey and in-depth interviews of key informants that was conducted in villages in three counties of two provinces in China. We assess the new decentralized service provision system for people living with HIV/AIDS in rural populations in China. Since 2003, new social assistance schemes, and, more importantly, decentralization of routine treatment and care to community health stations, were progressively implemented in rural areas most affected by the HIV/AIDS epidemic. Though some problems remain, such as persistent discrimination towards infected patients and the lack of sufficient training of medical staff, the new decentralized pattern of service provision has lowered barriers to health access and alleviated economic pressure on affected households.